Internal Factors Related to Pulmonary Function Status of Workers at UD X - Moh. Bastian (Universitas Airlangga, 2019)
Introduction: The processing of marble stone produces air pollution in the form of dust. Dust emission is generated from cutting, scraping, and polishing processes. The type of dust emission is Particulate Matter 2.5 (PM2.5). The dust level and exposure period can cause lung problems and respiratory complaints. The study aims to determine the factors related to the pulmonary function’s status of workers at UD X, Campurdarat Sub-district, Tulungagung District. Metods: This research used cross-sectional research design and quantitative approach. The sample of this study was 32 people consisting of 26 workers exposed to dust and 7 workers unexposed to dust. The independent variables include were gender, age, working period, education level, smoking habit, and use of Personal Protective Equipment (PPE). Results: In general, the pulmonary function of workers at UD X was quite good. Conlusion: The smoking habit and the use of PPE had a relationship with the pulmonary function of workers at UD X, Campurdarat Sub-district, Tulungagung District. Keywords: internal factor of worker, pulmonary function, workers